(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The notices relating the existence of a mountain with a plantation of olive-trees and consecrated to Aphrodite, during the Viriathus war, allow us to suppose the penetration of a Semitic cult between the peoples of the west of the Iberian peninsule, perhaps a cult of Astarte, which could amalgamate with some of the feminine paleohispanic divinities known through the epigraphy.